2020
DOI: 10.1021/acs.analchem.0c02823
|View full text |Cite
|
Sign up to set email alerts
|

Nanomolar Protein–Protein Interaction Monitoring with a Label-Free Protein-Probe Technique

Abstract: Protein–protein interactions (PPIs) are an essential part of correct cellular functionality, making them increasingly interesting drug targets. While Förster resonance energy transfer-based methods have traditionally been widely used for PPI studies, label-free techniques have recently drawn significant attention. These methods are ideal for studying PPIs, most importantly as there is no need for labeling of either interaction partner, reducing potential interferences and overall costs. Already, several differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Previously, we demonstrated the Eu 3+ -probe for monitoring protein stability and interactions and protease activity. 35 , 36 , 41 Here, we further developed the Protein-Probe method to detect mAb aggregates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we demonstrated the Eu 3+ -probe for monitoring protein stability and interactions and protease activity. 35 , 36 , 41 Here, we further developed the Protein-Probe method to detect mAb aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous findings related to protein-protein interactions, we assumed that these differences could be caused by varying levels of mAb aggregation in the samples. 36 The Protein-Probe method has a proven high sensitivity in the detection of protein denaturation, and we assumed it can also potentially monitor early aggregation. Our monitoring of six temperature-stressed mAbs at RT with the Protein-Probe indicated that these mAbs had different stability and susceptibility to aggregation ( Figure 3a ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Eu-probe was purified as described before, [31] and the concentration was determined using the DELFIA technique and a commercial EuCl 3 standard from PerkinElmer Life and Analytical Sciences, Wallac (Turku, Finland). The protein substrates, recombinant pertussis toxin (PTX), G protein alpha I subunit (Gαi) [33], human Ras GTPase-activating protein 1 (p120GAP) [34], wild type Kirsten RAt Sarcoma virus (KRAS, 2-188), human son of sevenless SOS1 catalytic domain (SOS cat , 564-1048) [35], and eukaryotic initiation factor 4A1 (eIF4A1) [32] were kind gifts from our collaborators. Malate dehydrogenase (MDH) was purchased from Roche (Basel, Switzerland).…”
Section: Materials Instrumentation and Assay Buffersmentioning
confidence: 99%